Pengaruh Komunikasi Efektif Dan Pelatihan Keterampilan Terhadap Produktivitas Karyawan Melalui Penggunaan Teknologi Sebagai Variabel Intervening Pada RSJ Prof. HB. Saanin Padang - Mega Dwimulia; Vicky Brama Kumbara; Chintya Ones Charli (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of effective communication and skills training on employee productivity with technology utilization as an intervening variable. The research uses a quantitative approach with Structural Equation Modeling based on Partial Least Square (SEM-PLS). The population consists of 378 employees, with a sample of 80 respondents determined using the Slovin formula and random sampling technique. Data were collected through Likert-scale questionnaires. Data analysis includes validity and reliability testing, outer model and inner model evaluation, and hypothesis testing using bootstrapping procedures. The results show that effective communication and skills training have a positive and significant effect on technology utilization. Effective communication and technology utilization have a positive and significant effect on employee productivity, while skills training does not have a significant direct effect on employee productivity. However, skills training has a positive and significant indirect effect on employee productivity through technology utilization as an intervening variable. The R-square values indicate that the model has strong explanatory power for technology utilization and employee productivity. These findings confirm that optimizing communication, training, and technology usage in an integrated manner can improve employee productivity.